The effect of polo drill swimming on freestyle kinematics: a pilot study - Brackley, V. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this pilot study was to compare temporal performance variables and kinematic parameters during the entry and catch phase of freestyle and Polo drill swimming. Five well-trained freestyle swimmers performed 400 m of Polo drill and freestyle through a 8.91 m3 calibrated space recorded by eight synchronised cameras. Differences were assessed by a paired t-test and effect size (d) calculations for each variable. Significant differences occurred with respect to stroke length, stroke rate, stroke duration, entry and catch duration, hip velocity and vertical displacement and trunk inclination. The finger displacement and velocity, elbow angle and shoulder displacement were not significantly different through the entry and catch phase of the stroke. This work identified that while notable differences exist between freestyle and Polo drill swimming, there is an indication that some key parameters may be similar.